Response surface optimization and flavor determination of fermentation processes of orange peel tea wine - Liu,Yanbo; Mengge,Liu; Zhang,Pengpeng; Liu,Wenxi; Yang,Chong; Cui,Jiayi; Li,Haideng; Pan,Chunmei (PeerJ, 2025)
Background In this study, Xinyang Maojian tea and orange peel were used as raw materials to brew health wine with orange and tea flavors. Methods Based on a single factor, the response surface method was used to optimize the fermentation of orange peel tea wine. Material volume ratio, yeast addition, fermentation temperature, fermentation time, and sucrose addition were used as the single-factor variables. The fermentation conditions of orange peel tea wine obtained by this method provide a theoretical basis for the development and utilization of tea wine and orange peel, which can promote the development of the tea wine market. Results The results showed that the material volume ratio of orange peel juice to tea juice was 1:3, the yeast addition amount was 4.9%, the fermentation temperature was 29 °C, the fermentation time was 7 d, and the sucrose addition amount was 29%. The main change indexes in the fermentation process of orange peel tea wine were determined, and the results were consistent with the fermentation law of orange peel tea wine. The contents of total flavonoids and total phenols in orange peel tea wine were 0.48 and 2.32 mg/mL, respectively, and were obtained using spectrophotometry and the Folin–Ciocalteu (F–C) method. The scavenging rate of 2,2-diphenyl-1-picrylhydrazyl (DPPH) radicals was 90.8%, and the scavenging rate of ·OH radicals was 77.3%. A total of 26 flavor compounds were detected by gas chromatography-mass spectrometry (GC-MS). The main aroma compounds were ethanol, 3-methyl-1-butanol, 2-methyl-1-propanol, phenylethyl alcohol, acetic acid, n-hexadecanoic acid, 2,4-di-tert-butylphenol, and other compounds. Conclusion The resulting orange peel tea wine was transparent, yellow in color, harmonious in flavor, and had certain health benefits, including strong antioxidant properties. The results of this study provide the theoretical basis for the research and development of tea wine.
Keywords: Orange peel tea wine; Response surface optimization; GC-MS; Fermentation